Project Based Environmental Education (PjBEE): Model pembelajaran inovatif untuk mengembangkan kompetensi keberlanjutan di kalangan calon guru - Pamungkas, Sekar; Rohman, Fatchur; Al Muhdhar, Mimien Henie Irawati; Novianti, Vivi (Biosfer: Jurnal Pendidikan Biologi, 2026)
The enhancement of students’ sustainability competencies remains a critical challenge in higher education. While project-based learning approaches have been effective in improving students’ problem-solving and collaboration abilities, their capacity to address complex environmental and sustainability issues is still limited. To overcome these limitations, this study developed and validated a Project-Based Environmental Education (PjBEE) model that integrates project-based learning with sustainability-oriented education. Employing a Research and Development (R&D), this study aimed to determine the model’s validity, practicality, and effectiveness in enhancing students’ sustainability competencies. The PjBEE model was implemented in environmental education courses and structured around six stages: Inquiring, Collaborating, Decision Making, Digital Action Planning, Creating Artifacts, and Action. Research instruments included expert validation sheets, observation sheets, student response questionnaires, and sustainability competency tests. The validation results confirmed that the PjBEE model met the criteria of high validity, feasibility, and practicality. Implementation findings demonstrated positive student engagement and significant improvement in sustainability competencies particularly in systems thinking, collaboration, strategic planning, and problem-solving. Therefore, the PjBEE model can serve as a pedagogically sound and empirically supported framework for integrating sustainability education into higher education curricula, particularly in biology teacher education programs.